The Use of Research-Based E-Flipbooks as Teaching Materials for Kingdom Monera - Supratman, Lilis (Pedagonal : Jurnal Ilmiah Pendidikan, 2023)
Cellulolytic bacteria in termites are adaptive symbionts in the digestive tract of termites. The purpose of making an e-flipbook is to make it easier for teachers to provide monera material with visualization media and to make it easier for students to understand the characteristics of cellulolytic bacteria. This research is a combination of qualitative and descriptive research. The results of cellulolytic bacteria research can be documented digitally in the form of an e-flipbook. E-flipbook is an alternative learning media that can help students to get a visualized picture of the material presented in a digital portable device. In the e-flipbook, it is outlined that cellulolytic bacteria have a significant physiological level. The test indicators use physiological tests, MR-VP tests and TSIA tests that produce the conclusion that cellulolytic bacteria in the termite GI tract are very suitable for the atmosphere of the GI tract. The feasibility test of the e-flipbook to be used as a learning resource has been validated by learning media experts and material experts. Validation results show an average of 91% resulting in valid criteria. The validation-based validator statement states e-flipbooks can be used as learning resources